The peculiarities for developing of apple scab’s pathogens in ascigerous stage and the disease expression in Western Forest-Steppe of Ukraine - Skoreyko, A.; Andriychuk, T.; Gunchak, M. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
The researches results for ascospore stage causative agent and disease appearing in Western Forest-steppe of Ukraine were provided.